2016
DOI: 10.3350/cmh.2016.0045
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of hepatocellular carcinoma risk in patients with chronic hepatitis B under antiviral therapy

Abstract: Hepatocellular carcinoma (HCC) is a primary concern for patients with chronic hepatitis B (CHB). Antiviral therapy has been reasonably the focus of interest for HCC prevention, with most studies reporting on the role of the chronologically preceding agents, interferon-alfa and lamivudine. The impact of interferon-alfa on the incidence of HCC is clearer in Asian patients and those with compensated cirrhosis, as several meta-analyses have consistently shown HCC risk reduction, compared to untreated patients. Nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 48 publications
2
58
0
2
Order By: Relevance
“…24,25 Long-term therapy with NAs appears to favourably impact HCC incidence when data from randomised or matched controlled studies are considered. 24,25 After the first 5 years of ETV or TDF therapy in CHB patients, recent data suggest that the HCC incidence is decreasing further, with the decrease being more evident in patients with baseline cirrhosis. 93 In addition, HCC seems to be the only factor affecting longterm survival in ETV or TDF treated CHB patients with or without compensated cirrhosis.…”
Section: Long-term Outcome During Na Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…24,25 Long-term therapy with NAs appears to favourably impact HCC incidence when data from randomised or matched controlled studies are considered. 24,25 After the first 5 years of ETV or TDF therapy in CHB patients, recent data suggest that the HCC incidence is decreasing further, with the decrease being more evident in patients with baseline cirrhosis. 93 In addition, HCC seems to be the only factor affecting longterm survival in ETV or TDF treated CHB patients with or without compensated cirrhosis.…”
Section: Long-term Outcome During Na Recommendationsmentioning
confidence: 99%
“…121 In addition, old cohort studies with standard IFNa and systematic reviews show that the incidence of HCC is decreased in IFNa treated compared to untreated CHB patients, with such an effect being clearer in Asian patients and those with sustained off-treatment responses and/or compensated cirrhosis. 1,24 Cohort studies in both HBeAg-positive and HBeAg-negative CHB have shown that courses of standard IFNa treatment result in improved overall long-term outcomes including survival in patients with sustained off-treatment responses. 1 Survival data are not available for PegIFNa therapy, but the same favourable outcomes are expected if sustained off-treatment responses are achieved.…”
Section: Long-term Outcome After Pegifna Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Along these lines, inhibiting the replication of HBV or completely eliminating HCV from the body could prevent hepatocarcinogenesis in patients with viral hepatitis. 9,[20][21][22] Several clinical trials and observational studies have reported the beneficial effects of antiviral treatment for preventing HCC through persistent viral suppression. 21,22 Although current antivirals' elimination effect on covalently closed circular DNA is imperfect, inhibiting viral replication and improving necroinflammatory activity using antivirals are expected to reduce substantially the risk of HCC in patients with chronic HBV infection.…”
Section: Secondary Preventionmentioning
confidence: 99%
“…Unfortunately, HCC may still develop. Previous studies have shown that long-term ETV or TDF monotherapy appears to favorably affect the incidence of HCC (8,10,11), especially in those patients, who have received more than 5 years of antiviral therapy (11). Since HCC seems to be the only predictive factor affecting long-term survival in-treated patients, the main clinical challenge is to identify the patients at risk of HCC who require close surveillance.…”
Section: Na Treatment For Chb Patientsmentioning
confidence: 99%